Pengembangan Koleksi Bahan Pustaka di Kantr Arsip, perpustakaan, dan Dokumentasi Kota Padang - Maulida, Rahmi; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
Based on data analysis can be concluded as follows: First, the process of the development of library collections in the Library at the Archives, Library and Documentation of Padang been developing library collections in the Library of the form; in the library collection development policy, the selection of library materials and procurement of library materials. Second, the obstacles encountered in implementing the development of library collections in the Archives, Library and Documentation city of Padang, namely, the lack of information catalog author, there is no room for the development of library collections, not maximal performance librarian and a lack of facilities and infrastructure. Third, efforts to overcome the obstacles in conducting the development of library collections in the Archives, Library and Documentation city of Padang, to add information from the authors, the library already has a special room for the development of library collections, should pay attention to infrastructure and facilities needed librarians, and librarians should own a clear division of tasks. Keywords: development,collectio